Pengaruh Lama Perendaman Ekstrak Bawang Merah dan Pemberian Pupuk Kotoran Sapi terhadap Pertumbuhan Stek Tanaman Mawar (Rosa Hybrida L.) - Jento Amardi; Desi Sri Pasca Sari Sembiring; Maimunah Siregar (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Propagation of rose plants through stem cuttings is a widely used method; however, its success is often influenced by the availability of adequate plant growth regulators and nutrients. The use of natural materials such as shallot extract as a source of plant growth regulators and cow manure as an organic fertilizer is expected to enhance the growth of cuttings in an environmentally friendly manner. This study aimed to determine the effect of soaking duration in shallot extract, the application of cow manure, and the interaction between both treatments on the growth of rose (Rosa hybrida L.) cuttings. The research was conducted in November 2025 in Sampe Cita Glugur Rimbun Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra, at an altitude of approximately 500 meters above sea level. The study employed a factorial Randomized Block Design with two treatment factors and three replications, resulting in 48 experimental units. The first factor was the soaking duration in shallot extract (0, 4, 8, and 12 hours), while the second factor was the dosage of cow manure (0, 50, 100, and 150 g per polybag). Observed parameters included survival percentage, time of shoot emergence, number of shoots, shoot length, number of leaves, and leaf length. The results showed that all treatments, both individually and in interaction, had no significant effect on all growth parameters. Nevertheless, plant growth increased with plant age, with a relatively high and uniform survival rate of approximately ±90%. These findings indicate that, at the treatment levels applied, shallot extract and cow manure were not effective in significantly improving the growth of rose cuttings, suggesting that further research with different concentrations or treatment combinations is needed.